Changes in Etiologies of Hospitalized Patients with Liver Cirrhosis in Beijing 302 Hospital from 2002 to 2013. (19th November 2017) - Chang, Binxia; Li, Baosen; Sun, Ying; Teng, Guangju; Huang, Ang; Li, Jin; Zou, Zhengsheng
Abstract : Background . Over the last 20 years, the prevalence of hepatitis B virus (HBV) infection in China has decreased gradually due to the application of a national HBV vaccination program. In contrast, the prevalence of alcoholic liver disease (ALD), nonalcoholic fatty liver disease, autoimmune liver disease, and drug-induced liver injury has markedly increased. Methods . We conducted a retrospective review of 82, 562 hospitalized patients diagnosed with liver cirrhosis in Beijing 302 Hospital from 2002 to 2013. Results . The top four etiologies of cirrhosis were HBV, HCV, ALD, and autoimmune liver disease. The percentage of HBV cirrhosis decreased from 81.53% in 2002 to 66.0% in 2013, whereas the frequency of alcoholic cirrhosis increased from 3.34% in 2002 to 8.40% in 2013. Females (84.34%) accounted for the majority of cirrhotic patients with autoimmune liver diseases. Males accounted for 80.16% of HBV cirrhosis patients and 98.02% of alcoholic cirrhosis patients. Conclusion . In Beijing 302 Hospital, the top four etiologies of cirrhosis were HBV, HCV, ALD, and autoimmune liver disease. Over the last 12 years, the prevalence of HBV cirrhosis has decreased gradually, whereas that of alcoholic cirrhosis has increased significantly.